The Influence Of DAU (General Allocation Fund) And DAK (Special Allocation Fund) On Capital Expenditure Of Bali Province - Suryantini, Ni Putu Santi (Economics and Business Solutions Journal, 2017)
Due to the governmental implementations and services to the public in accordance with the decentralization principle, the regional areas have the authority to collect taxes/levies and manage the Natural Resources (SDA). The regional areas funding sources consist of Own-Source Revenue (PAD), Fiscal Balance/Revenue Sharing Fund (DBH), General Allocation Fund (DAU) and Special Allocation Fund (DAK) which are directly managed by the regional government through its Regional Revenue and Expenditure Budget (APBD). This research aims at analyzing the influence of PAD, DAU, and DAK on capital expenditure of Bali province. The research population is all city/regency governments in Bali. This research employs a census method involving all Regencies and municipalities in Bali Province. The data are the regional government expenditure realization during the period of 2010 to 2015. The results show that PAD does not significantly influence Capital Expenditure, while DBH, DAU, and DAK significantly influence Capital Expenditure.